Space Eﬃciency of Technical Installations in Tall Oﬃce Buildings An early stage analysis based on HVAC, elevators, water distribution and ﬁre safety design - Erntoft, Henric; Lundberg, Tor (My University, 2019)
Tall buildings are becoming more common in Sweden and the progress will require knowledge within the ﬁeld. This thesis is aimed at an early stage analysis and investigates the technical systems for HVAC, elevators, water distribution and ﬁre safety design in tall oﬃce buildings with focus on space eﬃciency and the distribution of the systems. The thesis is meant to illustrate the importance of design choices rather than to provide optimized solutions. Information about relevant system choices was gathered through a literature study and by interviewing professionals within the ﬁeld. A case study was performed where three ﬁctitious buildings of increasing height were investigated. For each of the mentioned systems, a number of possible conﬁgurations were tested in all three buildings to investigate the eﬀects of increasing height and design choices on the space eﬃciency and the distribution of the systems. The results show that the space eﬃciencies of the studied systems are aﬀected diﬀerently by the building height and that some design choices are more beneﬁcial with respect to space eﬃciency. It was also evident that some of the systems have a greater potential of space saving than others. Additionally, it was seen that the distribution and sectioning vary between the systems depending on the requirements and prerequisites of each system. While it is recognized that many aspects need to be taken into account in a building project, the results in this report is considered to have the potential of being a support in an early stage analysis of tall oﬃce buildings.
Keywords: Tall oﬃce buildings; high-rise; space eﬃciency; HVAC; water distribution; elevators; ﬁre safety